Thinking out loud? Je me suis dit ‘I said to myself’ and j’étais là ‘I was there’ in French talk-in-interaction - Fiedler, Sophia (My University, 2023)
In this article, I investigate two, so far little studied, constructions from oral French that introduce direct reported thought: je me suis dit ‘I said to myself’ and j’étais là ‘I was there’. Whereas many studies target direct reported speech, research on direct reported thought remains sparse. Direct reported speech has been shown to allow speakers to display their affective stance during storytellings. I argue that in French talk-in-interaction, speakers can also use direct reported thought to take a stance. Drawing on Conversation Analysis and Interactional Linguistics, I analyzed 10h47min of video recordings of coffee breaks among students. The sequential analysis encompasses speech as well as the speakers’ bodily conduct including gaze, gesture, posture, and facial expressions. I show that j’étais là is used to take an affective stance in the ongoing talk, while being reenacted verbally, prosodically and bodily. In contrast, je me suis dit is used to take a rational stance by making publicly available a conclusion or decision that accounts for previous actions. This rational stance is not accompanied by a bodily reenactment. I thereby demonstrate that je me suis dit and j’étais là, when introducing direct reported thought, carry out distinct actions in talk-in-interaction. This result complements the growing body of research on a grammar-body-interface, and addresses a multimodal bifurcation in the rather novel research topic of direct reported thought.